The Need for Accessible Health Education - Laughlin, Michael K.; Benes, Sarah; Sherlock-Shangraw, Rebecca (Journal of Physical Education, Recreation and Dance, 2026)
Health education in preschool through 12th grade is an essential component of a well-rounded education and can positively impact student health and well-being. All school-age students deserve access to high-quality, effective health education. However, students with disabilities may not be receiving the health education they are entitled to for many reasons, including that there is not a clearly defined understanding of health education for students with disabilities. Working from the perspective that health education is both a social justice imperative and an important component of students’ “well-rounded education” under the Every Student Succeeds Act of 2015, this article is a call to action and brings attention to this area of need. It is framed around three critical questions: (1) Why do students with disabilities deserve access to health education? (2) How should health education for students with disabilities be conceptualized? (3) Where does accessible health education go from here? By articulating these questions and providing initial thoughts to spur further discussion and action, this article encourages invested partners and collaborators to address this critical need so that students with disabilities can meaningfully access the same high-quality health education opportunities as their peers. © 2026 SHAPE America.
Keywords: dept.hms

Testing Multiple Delivery Methods of the Virtual Exercise Games for Youth with T1D Peer Intervention: Protocol Development and Feasibility - Ash, Garrett I.; Nam, Soohyun; Mak, Selene S.; Stults-Kolehmainen, Matthew; Haughton, Adrian D.; Turek, Carolyn; Baker, Julien S.; Hieftje, Kimberly; Marks, Asher; Chmielewski, Annette; Shelver, Michael; Considine, Elizabeth G.; et al. (Hormone Research in Paediatrics, 2026)
Abstract – Introduction: Adolescents with type 1 diabetes (T1D) face barriers to moderate-to-vigorous physical activity (MVPA) such as uncertainty with self-management, limited access to supportive environments, and stigma related to living with diabetes. Opportunities for peer activities with T1D role model support are limited. To address this need, we tested iterative refinements of pilot Virtual Exercise Games for Youth with T1D (ExerT1D) for feasibility and acceptability. Methods: The program included 6 versions: study 1 (1.1–1.4) included an active video game, and study 2 (2.1–2.2) included a virtual reality (VR) active video game. All versions included T1D exercise management education by clinicians and goal-setting guided by young adult coaches with T1D. Results: Seventeen adolescents (median age 15.4 [IQR 14.6–16.4] years, 7 non-Hispanic white, 8 male, median HbA1c 8.1% [IQR 7.4%–11.1%]) were enrolled. Participants rated the program, comfort, clinicians, coaches, and group cohesion high/very high. Motivation for the video game was high. Building T1D and MVPA self-management skills was rated excellent at most sessions, as were peer interactions and enriched communication after adding immersive VR in study 2. Transitions between VR apps caused delays of 19 ± 6 min per 60 min–90 min session. Compared to baseline, HbA1c or glucose management indicator decreased over time in an exploratory analysis (d = −1.12, 90% CI: [−1.78, −0.48]). Conclusions: In a small cohort, the ExerT1D program facilitated a supportive environment for engaging diverse youth with T1D in an MVPA program led by T1D coaches. Larger studies are needed to assess the intervention’s impact on engagement with physical activity, glycemic outcomes, and quality of life. © 2026 S. Karger AG, Basel
Keywords: Diabetes; Peer support; Physical activity; Type 1; Video games; dept.hms

Introducing “Preservice Pipeline”—Why This Column, Why Now - Knipe, Bob (Journal of Physical Education, Recreation and Dance, 2026)
Future professionals learn to lead through a variety of professional opportunities, and it is time that JOPERD provides a forum dedicated to their development and an opportunity for them to lead as authors and coauthors. This article describes the new Preservice Pipeline column and how to submit articles. © 2026 SHAPE America.
Keywords: dept.hms

Testing multiple delivery methods of the virtual exercise games for youth with T1D peer intervention: protocol development and feasibility - Ash, Garrett; Nam, Soohyun; Mak, Selene; Stults-Kolehmainen, Matthew; Haughton, Adrian; Turek, Carolyn; Baker, Julien; Hieftje, Kimberly; Marks, Asher; Chmielewski, Annette; Shelver, Michael; Considine, Elizabeth; et al. (Hormone Research in Paediatrics, 2026)
INTRODUCTION: Adolescents with type 1 diabetes (T1D) face barriers to moderate-to-vigorous physical activity (MVPA) such as uncertainty with self-management, limited access to supportive environments, and stigma related to living with diabetes. Opportunities for peer activities with T1D role model support are limited. To address this need, we tested iterative refinements of pilot Virtual Exercise Games for Youth with T1D (ExerT1D) for feasibility and acceptability. METHODS: The program included 6 versions: study 1 (1.1-1.4) included an active video game, and study 2 (2.1-2.2) included a virtual reality (VR) active video game. All versions included T1D exercise management education by clinicians and goal-setting guided by young adult coaches with T1D. RESULTS: Seventeen adolescents (median age 15.4 [IQR 14.6-16.4] years, 7 non-Hispanic white, 8 male, median HbA1c 8.1% [IQR 7.4%-11.1%]) were enrolled. Participants rated the program, comfort, clinicians, coaches, and group cohesion high/very high. Motivation for the video game was high. Building T1D and MVPA self-management skills was rated excellent at most sessions, as were peer interactions and enriched communication after adding immersive VR in study 2. Transitions between VR apps caused delays of 19 ± 6 min per 60 min-90 min session. Compared to baseline, HbA1c or glucose management indicator decreased over time in an exploratory analysis (d = -1.12, 90% CI: [-1.78, -0.48]). CONCLUSIONS: In a small cohort, the ExerT1D program facilitated a supportive environment for engaging diverse youth with T1D in an MVPA program led by T1D coaches. Larger studies are needed to assess the intervention's impact on engagement with physical activity, glycemic outcomes, and quality of life.
Keywords: Glycemic; Physical activity; Program evaluation; Protocol (science); Quality (philosophy); Quality of life (healthcare); dept.hms

National Trends in Athletic Training Service Provision in U.S. High Schools: A Five-Year Longitudinal Assessment - Kim, D; Eason, Christianne; Grubb, Joseph; Casa, Douglas; Coleman, Kelly; Filep, Erica; Huggins, Robert (Current Sports Medicine Reports, 2026)
Keywords: Athletes; Athletic training; Sports medicine; Trainer; Training (meteorology); dept.hms

Forgotten Learners: High School Transition Students With Disabilities - Laughlin, Michael K. (Journal of Physical Education, Recreation and Dance, 2026)
Because physical literacy and activity are not emphasized in special education as they are in physical education or adapted physical education (PE/APE), this editorial explores two important questions: Do high school transition students receive PE/APE programming? And are PE/APE teachers introduced or exposed to transition services at any point in their teacher training?. © 2026 SHAPE America.
Keywords: dept.hms

Remote Lesson Study as Continuing Professional Development for Physical Education Teachers - Colburn, Jeffrey; Knipe, Robert; Doherty, Brooke; Stephenson, Rachyl; Hamilton, Xiaofen (Journal of Teaching in Physical Education, 2026)
Purpose: This study investigated experiences of physical education teachers (PETs) participating in online remote andragogy-based lesson study (AbLS) during a pandemic. Method: Five PETs participated in this phenomenological case study. Seventeen online AbLS collaborative meetings took place via Zoom software. Three rounds of semistructured interviews were conducted and analyzed using collaborative qualitative analysis. Results: Three themes emerged: (a) AbLS facilitated depth of learning, increasing professional and individual growth; (b) AbLS structure influenced experience; and (c) the professional community of AbLS supported a natural adult learning (andragogical) environment. Discussion/Conclusion: Remote AbLS presented benefits for these PETs beyond professional learning that prior continuing professional development had not, including a sense of community, belonging, and professional worth. AbLS may have implications for research in perceived mattering and continuing professional development facilitation for PETs. Remote AbLS may bolster PETs in challenging local learning communities. © 2026 Human Kinetics, Inc.
Keywords: andragogy; dept.hms; marginalization; professional learning; remote communities